DETERMINAN TERHADAP KECENDERUNGAN NILAI RUJUKAN GURU PENDIDIKAN JASMANI - Adang Suherman (LPMPP Universitas Negeri Yogyakarta, 2010)
Abstract: Effects of School Context Variables on Physical Education TeachersValue Orientation. A school is a laboratory for teachers to implement a variety ofprofessional competencies. The condition of a school can inhibit or support them torealize their potentials. Teachers knowledge, understanding, attitudes, willingness,and value orientation are believed to determine the success of the curriculumimplementation. This study aims to find out how the school conditions affect thetendency of physical education teachers value orientation. This study used asample of 30 physical education teachers at primary schools, purposively selected.The data were collected using the Value Orientation Inventory (VOI) developed byEnnis and Chen. The results show that class sizes, facilities, and socialenvironments affect the types of TVO that teachers inculcate to students throughthe teaching and learning process. However, the students conditions do not affectthe types of TVO.Keywords: class sizes, facilities, social environments, students conditions, teacher value orientation